Referral Healthcare Services and Efficiency of Indonesian Health Insurance on Patient Satisfaction and Life Quality - Alfarizi, Muhammad; Arifian, Rafialdo; Noer, Lissa Rosdiana (BPJS Kesehatan, 2024)
The UN's Sustainable Development Goals (SDGs) target Universal Health Coverage (UHC) to ensure equitable access to health without financial burden. The National Health Insurance Program-Healthy Indonesia Card (JKN-KIS) by BPJS Kesehatan seeks to meet the health needs of the Indonesian people, especially vulnerable groups, including in East Java, which faces many cases of catastrophic diseases. This study aims to analyse the impact of the quality of referral health services and the efficiency of insurance administration on the satisfaction and quality of life of catastrophic patients in East Java. This study uses a positivist quantitative approach with a questionnaire-based Cross-Sectional design to collect data from outpatient catastrophic patients in East Java. Two hundred sixty-three responses were analysed using the PLS-SEM technique through SmartPLS 4.0 software to test hypotheses regarding the quality of referral services, insurance administration, patient satisfaction, and quality of life. The results showed that the ease of JKN-KIS administration significantly affected participant satisfaction, corroborating previous findings regarding the importance of easy access and simple administrative procedures in increasing the positive perception of services. In addition, the quality of referral health facility services also increases satisfaction, especially in meeting the care needs of catastrophic patients. Satisfaction with JKN-KIS also significantly impacts patients' quality of life, improving their physical health, emotional stability, and social satisfaction. These findings encourage optimising JKN-KIS services through digitisation and improving the quality of special services for catastrophic patients to maintain participant satisfaction and trust